Online marketing fundamentals : 10 SEO myths busted - Bailey, Matt, 1969- (FT Press, 2013)
"You've heard those pieces of advice that try to pass as SEO secrets, but listen up. There's a lot of misinformation out there, and if you're not careful, you can waste valuable time, energy, and budget chasing rainbows. Discover fairy tales worth ignoring when SEO expert Matt Bailey debunks his top 10 myths of search engine optimization. Topics covered in this workshop include: why getting the No. 1 spot is not always the most business-savvy move; what are outdated SEO optimization strategies, and why; how SEO has changed in today's search engines; and why "R.I.P SEO" may not be a myth."--Resource description page.